Pengenalan Oximeter sebagai Deteksi Kejenuhan Oksigen dalam Darah Kepada Satgas Covid-19 Kalurahan Serut, Gunung Kidul - Umi Salamah; Damar Yoga Kusuma (Indonesian Journal of Community Empowerment and Service (ICOMES), 2021)
Since the emergence of Covid-19 in Indonesia in early 2020, it has spread throughout Indonesia, including rural areas. The Serut District, which is a border area, namely the Klaten district with Gunung Kidul, cannot be separated from the spread of Covid-19. The condition of the people of Serut Village, which is a genuine rural community, causes a lack of understanding of the dangers of the virus. The confusion of news in the mass media and social media has made the understanding of Covid-19 blurry. One of them is a non-invasive oxygen saturation detection system technology using an oximeter to monitor blood health conditions. This is very important, especially for patients who have confirmed Covid-19 and are self-isolating at home. In this service, the implementing team collaborates with the Serut Village government and the ranks of the Covid-19 task force to mitigate Covid-19 in the Serut Village area. The programs that will be implemented include providing materials and demonstrations for detecting oxygen saturation in the blood using an oximeter to the Covid-19 task force. The provision of materials and demonstrations will be continued with data sampling and analysis to the people of Serut Village. This program aims to introduce the system of measuring oxygen saturation in the blood and how to measure it independently. This is very important considering that oxygen saturation in the blood is one of the parameters in Covid-19 patients.  Keywords:  Oximeter; Blood Oxygen Saturation ;Satgas Covid-19; Kalurahan Serut